Peralihan Bahasa Kaum Iban di Negara Brunei Darussalam - Damit, Ashrol Rahimy; Lalu Nurul Yaqin; Rusdi, Aieza Surieana; Amirul Syafiee, Amieziezaitul Syazlien Ezzeq Ezrynah; Abdullah Sofian, Serianie (Journal Ilmiah Rinjani : Media Informasi Ilmiah Universitas Gunung Rinjani, 2024)
This study aims to examine the phenomenon of language transition that occurs among the Iban people in Brunei Darussalam. The inquiry method is used to identify patterns of language transition. The findings of this investigation found that although Iban is still the main language, it is slowly being replaced by Brunei Malay. Among the causes are mixed marriages between the Iban tribe and other tribes, migration to new places due to work incentives or mixed marriages, and social communication factors that prioritize the Bruneian Malay language. There is awareness among the respondents and they have a positive attitude towards their mother tongue. The majority of them hope that the Iban language will continue to be maintained and used. They also stated that it would be a loss if their mother tongue disappeared. This positive language attitude is reflected in those who continue to use Iban, where they feel proud to speak it even in public places. ABSTRAK Kajian ini bertujuan untuk meneliti fenomena peralihan bahasa yang berlaku dalam kalangan kaum Iban di Negara Brunei Darussalam. Metode kaji selidik digunakan dalam mengidentifikasi pola peralihan bahasa. Penemuan penyelidikan ini mendapati meskipun bahasa Iban masih menjadi bahasa utama namun bahasa tersebut perlahan-lahan diganti oleh bahasa Melayu Brunei. Antara penyebabnya ialah kahwin campur antara puak Iban dengan puak lain, migrasi ke tempat baharu atas dorongan pekerjaan atau kahwin campur, dan faktor komunikasi sosial yang mengutamakan bahasa Melayu Brunei. Terdapat kesedaran dalam kalangan responden dan mereka memiliki sikap positif terhadap bahasa ibunda mereka. Majoriti mereka berharap agar bahasa Iban terus dipelihara dan digunakan. Mereka juga menyatakan adalah satu kerugian jika bahasa ibunda mereka pupus. Sikap bahasa yang positif ini tercermin dalam kalangan mereka yang kekal menggunakan bahasa Iban di mana mereka merasa bangga untuk menuturkannya meskipun di tempat awam. Keywords: Language switching; Language extinction; Iban language; The Iban; Brunei Darussalam